A study on the dynamic evolutionary processes of blockchain-enabled transnational low-carbon technology collaboration - Li, Yan; Wu, Jun; Li, Boying (Frontiers in Physics, 2025)
IntroductionIn the context of the global shift toward a multi-level networked climate governance system, multinational enterprises (MNEs) and local firms’ collaboration on low-carbon technologies has become a critical pathway to address imbalances in emission reduction responsibilities and regional institutional conflicts. However, regional institutional differences and the risk of opportunism in technology transfer pose challenges to cooperation efficiency and market integration.MethodsTo tackle these issues, this paper constructs a tripartite evolutionary game model encompassing MNEs, local firms, and blockchain platforms. The research focuses on three core characteristics of blockchain technology: decentralisation, immutability, and the automated execution of smart contracts. These properties enable the transformation of divergent regional institutional frameworks into trustworthy, self-enforcing on-chain protocols. This mechanism aims to mitigate bilateral opportunism risks during collaboration while providing robust technical underpinnings for dynamic incentive mechanisms. The study specifically delves into how blockchain reshapes the competitive-collaborative equilibrium between MNEs and local firms.ResultsThe findings indicate that enterprises’ cooperation willingness and blockchain platforms’ regulatory enthusiasm are key drivers of cross-border emission reductions. Specifically, blockchain can effectively reduce opportunistic behavior, thereby enhancing cooperation willingness. A higher reputation capital of blockchain platforms promotes cooperation, whereas excessive cost reductions may have the opposite effect. Furthermore, opportunistic gains and technology spillover effects significantly influence cooperation willingness. The analysis also reveals that dynamic reward-punishment strategies are more effective than static ones in promoting collaboration and optimizing the system.DiscussionThis research offers theoretical support and practical guidance for resolving cross-border emission reduction dilemmas, optimizing blockchain platform governance, and fostering the development of a global low-carbon technology innovation network.